Respuesta :
Answer:
(k ∘ p)(x)=2x^2-12x+13
Step-by-step explanation:
(k ∘ p)(x)=k(p(x))
(k ∘ p)(x)=k(x-3)
(k ∘ p)(x)=2(x-3)^2-5
(k ∘ p)(x)=2(x-3)(x-3)-5
Use foil on (x-3)(x-3) or use this as a formula:
(x+a)^2=x^2+2ax+a^2.
(k ∘ p)(x)=k(p(x))
(k ∘ p)(x)=k(x-3)
(k ∘ p)(x)=2(x-3)^2-5
(k ∘ p)(x)=2(x-3)(x-3)-5
(k ∘ p)(x)=2(x^2-6x+9)-5
Distribute: multiply terms inside ( ) by 2:
(k ∘ p)(x)=2x^2-12x+18-5
(k ∘ p)(x)=2x^2-12x+13
The composite function is [tex]k(p(x))=2x^{2} -12x+13[/tex]
Option b is correct.
Composite function :
Given function are,
[tex]k(x)=2x^{2} -5,p(x)=(x-3)[/tex]
We have to find composite function [tex]k(p(x))[/tex].
[tex]k(p(x))=k(x-3)\\\\k(p(x))=2(x-3)^{2}-5\\ \\k(p(x))=2(x^{2} +9-6x)-5\\\\k(p(x))=2x^{2} +18-12x-5\\\\k(p(x))=2x^{2} -12x+13[/tex]
Thus, the composite function is [tex]k(p(x))=2x^{2} -12x+13[/tex]
Learn more about the composite function here:
https://brainly.com/question/10687170